Efficacy of Estrus Synchronization Protocols during Summer and Winter Seasons together with Biochemical and Minerals Profile in Anoestrus Crossbred Cows - Borakhatariya, D.N.; Panchal, M.T.; Dhami, A.J.; Hadiya, K.K.; Kalasariya , R.M. (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
The estrus induction and fertility response along with biochemical and minerals profile of >90 days postpartum anoestrus crossbred cows following use of different estrus synchronization protocols was investigated during summer and winter seasons. The true anoestrus cows selected (n=43 in summer, n=40 in winter) were randomly treated with Ovsynch, Heatsynch and PRID protocols keeping 10 animals as control in both the seasons. During summer season, the estrus induction response with Ovsynch, Heatsynch and PRID protocol was 80, 90 and 80 %; while in winter season, the response was 100% with all three protocols. In summer season, the conception rates with Ovsynch, Heatsynch and PRID protocols at induced estrus were 30, 20 and 20 %and those of 3 cycles 60, 40 and 50 %, respectively, while in winter season, the conception rates at induced estrus were 45.45, 27.27 and 36.36 % and overall of 3 cycles 72.72, 45.45 and 63.64%, respectively. The overall mean plasma concentrations of total cholesterol (mg/dl) in anoestrus cows under Ovsynch, Heatsynch and PRID protocols were 171.57±4.75, 190.97±4.90 and 184.93±3.10 during winter and 163.73±4.96, 162.87±11.24 and 177.63±7.98 during summer, respectively. The corresponding values for plasma total protein (g/dl) during winter season were 7.77±0.11, 7.90±0.12and7.51±0.14, and in summer season 7.90±0.14, 8.02±0.67 and 8.32±0.10, respectively. The cholesterol levels were insignificantly lower and protein levels were significantly higher in summer than winter season, particularly in non-conceived cows. Among the minerals profiles, i.e. calcium, phosphorus and magnesium, only the calcium levels were significantly higher during winter and in conceived cows as compared to counter parts. In conclusion, the results showed that estrus synchronization with fixed time insemination protocols can augment fertility in anoestrus crossbred cows under favorable as well as heat stress condition, and the response is better with Ovsynch and PRID protocols without influencing much the blood metabolic profile.